PENGARUH PEMAHAMAN SAINS ISLAM PESERTA DIDIK TERHADAP PERILAKU KEAGAMAAN - Akhmad Wahyudi (Program Studi Magister Pendidikan Agama Islam, Sekolah Pascasarjana Universitas Ibn Khaldun Bogor, 2018)
As stated in Law No. 20 of 2003 Article 3 that the objectives of National Education are to develop the potential of students to become human beings who believe and devote to God Almighty, have noble character, are healthy, knowledgeable, capable, creative, independent, and become democratic and responsible citizens. This shows that giving the values of faith is the main goal of education in Indonesia so that all learning processes must be based on this goal, especially in Science learning at school. This study aims to determine the effect of students 'understanding of Islamic Science and its influence on students' religious behavior. The method used is quantitative survey research methods that use descriptive statistical data analysis techniques, bivariate correlation and multiple linear regressions. The study was conducted on 250 students grade IX of Public and Private Middle Schools scattered in the Ciampea sub-district. The results of the study indicate that there is a significant influence on students 'understanding of Islamic Science on the religious behavior of students. The result is the understanding of Islamic Science is positively related to students' religious behavior. So that, it can be said that the higher the level of understanding of Islamic Science, the higher the religious behavior of students.